Analisa Jartest Untuk Mengetahui Dosis Optimum Harian Poly Aluminium Chloride (PAC) di PDAM Krian - Muhammad Hisyam Fauzan; Munawar Ali (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Clean water is one of the most basic needs of humans as it is constantly needed in their daily activities to survive. The aim of this study is to ensure the correct dosage of Poly Aluminium Chloride (PAC) for at a certain level of rigidity and to avoid chemical waste. Overall, data analysis shows that the water quality in IPA Krian is well awake and in line with applicable standards. This reflects an effective water quality management and monitoring system at the site, with proper adjustment of the fluorescent dosage and the implementation of an efficient water management system.